2006
DOI: 10.1140/epjb/e2006-00398-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-mediated binding between holes in an antiferromagnet

Abstract: The long-range forces between holes in an antiferromagnet are due to magnon exchange. The one-magnon exchange potential between two holes is proportional to cos(2ϕ)/ r 2 where r is the distance vector of the holes and ϕ is the angle between r and an axis of the square crystal lattice. One-magnon exchange leads to bound states of holes with antiparallel spins resembling d-wave symmetry. The role of these bound states as potential candidates for the preformed Cooper pairs of high-temperature superconductivity is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…In this section we calculate the one-magnon exchange potentials between holes and we solve the corresponding two-hole Schrödinger equations. The one-magnon exchange potentials as well as the solution of the Schrödinger equation for a hole pair of flavors α and β were already discussed in [79]. Here we present a more detailed derivation of these results and we extend the discussion to hole pairs of the same flavor.…”
Section: Magnon-mediated Binding Between Holesmentioning
confidence: 73%
See 1 more Smart Citation
“…In this section we calculate the one-magnon exchange potentials between holes and we solve the corresponding two-hole Schrödinger equations. The one-magnon exchange potentials as well as the solution of the Schrödinger equation for a hole pair of flavors α and β were already discussed in [79]. Here we present a more detailed derivation of these results and we extend the discussion to hole pairs of the same flavor.…”
Section: Magnon-mediated Binding Between Holesmentioning
confidence: 73%
“…The location of the hole pockets has an important effect on the dynamics and implies d-wave characteristics of hole pairs. Using the methods described in this paper, analogous to applications of baryon chiral perturbation theory to few-nucleon systems [69,70,71,72,73,74,75,76,77,78], we have recently investigated magnon-mediated binding between two holes residing in two different hole pockets [79]. Here we discuss these issues in more detail and we extend the investigation to a pair of holes in the same pocket.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using the effective theory, we have shown that the one-magnon exchange potential between two isolated holes gives rise to binding with d-wave characteristics [71,76]. In a spiral phase the exchange of spiral phonons (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we have used the effective theory to derive the magnon-mediated forces between two isolated holes in an otherwise undoped system [71,76]. Remarkably, the Schrödinger equation corresponding to the one-magnon exchange potential can be solved analytically and gives rise to an infinite number of bound states.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the success of baryon chiral perturbation theory for QCD, a systematic low-energy effective field theory for magnons and holes in an antiferromagnet on the square lattice was constructed in [13,14]. This theory has been used in a detailed analysis of twohole states bound by one-magnon exchange [14,15] as well as of spiral phases in the staggered magnetization [16], which are a condensed matter analog of pion condensation in dense nuclear matter. The systematic effective field theory investigations have also been extended to electron-…”
Section: Effective Field Theory For Holes and Magnonsmentioning
confidence: 99%